Towards Malaysia MADANI: Do Leadership Styles Influence Innovative Work Behavior? A Conceptual Framework for the Malaysian Public Sector - Abidin, Zuliana Zainol; Arham, Ahmad Fadhly; Abdul, Shaiful Azlan; Ahmad, Hal Mahera (Information Management and Business Review, 2024)
Transformational leadership, known for inspiring and motivating employees, has been positively linked to creativity and innovation, while ambidextrous leadership, which balances exploration and exploitation behaviors and supports both idea generation and implementation. This article provides a conceptual framework for the influence of transformational and ambidextrous leadership on innovative work behavior (IWB) among PTD officers as middle managers in Malaysian public service. The first proposition is transformational leadership positively influences innovative work behavior. The second proposition is ambidextrous leadership positively influences innovative work behavior. This model will be further tested using a quantitative research method, survey questionnaires and analyzed using SPSS and PLS-SEM. Accordingly, understanding of IWB in public sector settings is enhanced. The findings demonstrate the application of Social Cognitive Theory (SCT) and thus offer new theoretical insights and practical suggestions. Thus, this study highlights the importance of work behavior that drives innovation and positive values among employees in determining productivity and efficiency in the public sector, offering valuable insights for policymakers and practitioners.